Evaluation of Pd composite membrane for pre-combustion CO2 capture. (February 2015) - Goldbach, Andreas; Bao, Feng; Qi, Chenchen; Bao, Chun; Zhao, Lingfang; Hao, Chuanyong; Jiang, Chunhai; Xu, Hengyong
Highlights: 150 day high-pressure natural gas reformate separation test. 98% carbon capture with 98% hydrogen recovery at 99.5% purity. Mechanical membrane stabilization through void structure evolution. Steam essential for minimizing carbon deposition. Abstract: Carbon capture with hydrogen-selective Pd membranes can be realized as highly integrated process and CO2 can be separated at high pressure without employing environmentally harmful sorption agents. This study investigates the technical viability of using ultrathin Pd/ceramic composite membranes with innovative ceramic-to-metal connections under conditions that are practically interesting for natural gas-fired power stations, i.e. high feed and permeate pressures and high H2 recovery at elevated temperature. The 90% CO2 capture target was well exceeded during a 150 day test in water gas-shifted reformate at 673 K. After system stabilization 98% carbon were held back by the membrane while 98% H2 were separated at nominally 99.5% H2 purity. Special attention has been paid to long-term operation effects on the 2–4 μm thick Pd layer. These include the development of a striking, cavernous Pd morphology which increases mechanical stability of the composite membrane, a somewhat reduced but steady H2 permeability, and the disappearance of most membrane defects. The latter is attributed to carbon deposits as exit flow analyses point to CO2 reduction preserving effectively membrane selectivity. Altogether, carbon capture with supported Pd membranes projects as feasible from a technological vantage point.